2019
DOI: 10.3892/mmr.2019.10165
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the aberrantly expressed lncRNA‑associated ceRNA network in breast cancer

Abstract: Previous studies have suggested that long non-coding RNAs (lncRNAs) are closely associated with human diseases, particularly cancer, including cancer of the lung, breast and stomach. A variety of lncRNAs are abnormally expressed in cancer and participate in several pathways including cell proliferation and apoptosis; these elements are closely associated with the development of cancer. The Cancer Genome Atlas (TCGA) is an important cancer database. It consists of clinical data, genomic variation, mRNA, microRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 45 publications
3
31
0
Order By: Relevance
“…Among the recently appreciated genes in this regard are long non-coding RNAs (lncRNAs) 6 . These transcripts are involved in the regulation of fundamental cell survival pathways and have functional interactions with proteins and other non-coding RNAs that participate in the pathogenesis of breast cancer 7 . Identification of such networks is an important step towards design of targeted therapies in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Among the recently appreciated genes in this regard are long non-coding RNAs (lncRNAs) 6 . These transcripts are involved in the regulation of fundamental cell survival pathways and have functional interactions with proteins and other non-coding RNAs that participate in the pathogenesis of breast cancer 7 . Identification of such networks is an important step towards design of targeted therapies in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This publicly available database provides over 20,000 primary tumor and matched normal samples spanning 33 cancer types. Researches based on this database have already led to improvements of diagnosis, prevention and treatment for cancers [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we revealed a role of 3 ′ US-ceRNA effect on HK genes. In the cancer context, the potential for being ceRNA was identified for mRNAs [e.g., (Tay et al, 2011)] as well as long non-coding RNAs [e.g., (Tuersong et al, 2019)] and pseudogenes [e.g., (Wei et al, 2017)]. Among mRNAs, it has been shown that TA genes and TF genes heavily contribute to ceRNA regulation (Sumazin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%